EXPLORING DIGITAL INNOVATION CAPABILITIES IN MSMES AGROSOCIOPRENEURSHIP : AN ENTREPRENEURIAL ECOSYSTEM PERSPECTIVE - Nanis Hairunisya; Syaiful Arifin; Anis Zubair (Adisam Publisher, 2025)
Digital transformation is a strategic factor for agrosociopreneurial MSMEs to enhance competitiveness and business sustainability . This study aims to develop a conceptual model explaining the relationships between the Digital Entrepreneurial Ecosystem (DEE), Innovation Capability (IC), and Business Performance (BP). An exploratory – theoretical design was employed using bibliometric and systematic literature review (SLR) methods . Data were analyzed using VOSviewer for trend mapping and Co- occurrence Matrix. The study population compressed scientific publications , industry reports , and experts and academics in digital innovation , green economy , and MSME development , with a sample consisting of research articles from the past ten years and ten purposively selected experts . The findings indicate that DEE plays a crucial role in enhancing the innovation capability of agrosociopreneurial MSMEs . Value co-creation is identified as a key mechanism mediating the DEE–IC relationship and potentially strengthening the impact of DEE when stakeholders engagement is high . The proposed conceptual model provides a theoretical contribution by integrating DEE, co-creation , and IC, as well as practical recommendations to strengthen digital collaboration , technological literacy , and innovation policies for MSMEs .